P5-S6.06 Utilisation and cost of diagnostic methods for STD screening among insured American Youth, 2008. (10th July 2011) - Owusu-Edusei, K; Nguyen, H; Gift, T
Abstract : Background: Information on the private sector utilisation and cost of sexually transmitted disease (STD) screening and diagnostic testing in the USA is limited. We present STD diagnostic method-specific utilisation and cost estimates for persons aged 15–25 years. Methods: We used current procedural terminology (CPT) (or diagnostic methods) codes for seven major STDs (human papillomavirus (HPV), genital herpes simplex virus type 2 (HSV-2), hepatitis B virus (HBV), chlamydia (CT), gonorrhoea (GC), trichomoniasis (TV) and syphilis) to identify outpatient claims for persons aged 15–25 years in the MarketScan database for 2008, excluding codes for procedures that could be used to identify claims for non-STD-related tests. Utilisation was measured as the number of claims per 100 000 enrollees (ie, claims rate). We estimated CPT code-specific claims rates for each STD and average costs stratified by gender. Finally, we estimated the overall total cost of STD testing. Results: We found 24 CPT codes for HPV; 2 for HSV-2; 11 for HBV; 9 for CT; 4 for GC; 2 for TV; and 5 for syphilis. The claims rate (all diagnostic methods included) for HPV was the highest (17 239/100 000, significantly higher (p<0.01) than all the STDs), while the claims rate (all testing methods included) for TV was the lowest (507/100 000, significantly lower (p<0.01) than all the STDs). Claims rates (for all STDs combined) for females were significantly (p<0.01) higher than for males for all the STDs. Estimated average costs (for diagnostic methods) were: HPV (35), HSV-2 (24), HBV (32), CT (46), GC (45), TV (30), and syphilis (29). Average costs did not differ significantly between males and females. The estimated total cost of screening for all seven STDs was 90 million for the insured population aged 15–25 years. Conclusions: The claims data provide an estimate of STD testing patterns among privately-insured persons. These can be compared to surveillance data and guidelines to assess testing vs disease prevalence and recommendations. The low utilisation rates we assessed for TV are likely attributable, at least in part, to our exclusion of claims that could be related to non-STD-related tests (such as wet mount). The low utilisation rates might also reflect the lack of attention to TV in STD prevention that has been reported in the literature.